The praxis of combating VAW in Ethiopia: A political interpretation - Dereje Feyissa (Danish Institute for International Studies (DIIS), 2020)
Violence against Women (VAW) is among the human rights violations that women face globally every day. The roots of VAW lie in historically unequal power relations between men and women and pervasive discrimination against women in both the public and private spheres. VAW is a global phenomenon that is not limited to certain cultures or countries. However, the form it takes is context-specific. In Ethiopia VAW is pervasive, occurring at three levels as identified by the UN: family; community; and the state. Despite policy pronouncements and the implementation of some practical measures, VAW is still prevalent in Ethiopia. This new Working Paper by Dereje Feyissa, adjunct associate professor, Addis Ababa University, offers a political interpretation to explain the gap between policy and practice on VAW in Ethiopia. Specifically, it argues that the gap between policy and practice lies in the type of regime in Ethiopia, which has undermined the political will and limited the space for gender activism. Historically, this has been evident ideologically (the Marxist frame of the 'women question' and the vanguardism connected with it), but also in respect to political legitimacy (ethnic federalism and the priority given to cultural rights), entrenched authoritarianism and the limited space available for gender activism by women's right groups.
Keywords: 330; Gewalt; Frauen; Geschlechterdiskriminierung; Frauenpolitik; Äthiopien